Wine and music (II): can you taste the music? Modulating the experience of wine through music and sound - Spence, C; Wang, Q (BioMed Central, 2015)
A growing body of scientific evidence now shows that what people taste when evaluating a wine, and how much they enjoy the experience, can be influenced by the music that happens to be playing at the same time. It has long been known that what we hear can influence the hedonic aspects of tasting. However, what the latest research now shows is that by playing the “right” music one can also impact specific sensory-discriminative aspects of tasting as well. Music has been shown to influence the perceived acidity, sweetness, fruitiness, astringency, and length of wine. We argue against an account of such results in terms of synaesthesia, or “oenesthesia,” as some have chosen to call it. Instead, we suggest that attention, directed via the crossmodal correspondences that exist between sound and taste (in the popular meaning of the term, i.e., flavor), can modify (perhaps enhance, or certainly highlight when attended, or suppress when unattended) certain elements in the complex tasting experience that is drinking wine. We also highlight the likely role played by any change in the mood or emotional state of the person listening to the music on taste/aroma perception as well. Finally, we highlight how the crossmodal masking of sweetness perception may come into effect if the music happens to be too loud (a form of crossmodal sensory masking). Taken together, the evidence reviewed here supports the claim that, strange though it may seem, what we hear (specifically in terms of music) really can change our perception of the taste of wine, not to mention how much we enjoy the experience. Several plausible mechanisms that may underlie such crossmodal effects are outlined.